Respuesta :

Answer:

This equation is invalid.

Step-by-step explanation:

3(4x-1)=6(2x-5)

We simplify the equation to the form, which is simple to understand  

3(4x-1)=6(2x-5)

Reorder the terms in parentheses

+(+12x-3)=6*(2x-5)

Remove unnecessary parentheses

+12x-3=+6+*(+2x-5+)

Reorder the terms in parentheses

+12x-3=+(+12x-30)

Remove unnecessary parentheses

+12x-3=+12x-30

We move all terms containing x to the left and all other terms to the right.  

+12x-12x=-30+3

We simplify left and right side of the equation.  

0x=-27

0=-27

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

ACCESS MORE